FATIGUE IN RHEUMATOID ARTHRITIS REFLECTS PAIN, NOT DISEASE ACTIVITY (The Research of Medical Science Review, 2025)
Objective: To observe the relationship between pain and fatigue in Rheumatoid Arthritis patients.Study Design: A Cross sectional observational studyStudy Duration: 06 months Study Place: Tertiary Care Hospital, LahoreMethods: A cross-sectional observational study was conducted over six months in the Rheumatology Department of a tertiary care hospital in Lahore. 200 patients were enrolled in the study after taking informed consent. Data were analyzed using SPSS 25, with significance set at p<0.05. Ethical approval was obtained beforehand.Results: 200 patients were enrolled in the study, and among them were 90 males and were 110 females. Fatigue was present in 191 patients and pain alongside in 127 patients. Fatigue and pain have strong corealtion. ESR and CRP did not correspond with the symptoms of pain. Among 200 patients, fatigue was more prevalent in females and pain was more present in males.Conclusion: Rheumatoid arthritis (RA) Fatigue is a multifactorial symptom complicated by chronic pain and fatigue. Thus, the effective measures towards fatigue management must be multidimensional and patient-focused to integrate anti-inflammatory treatment with pain, and mental and psychosocial support. Such a comprehensive approach presents the greatest chance to improve the fatigue level and the overall life quality of people with RA..